Conceptualization and Intervention Skills for Effective Helping - Okun, Barbara F.; Suyemoto, Karen L. (Belmont, California : Brooks Cole/Cengage Learning, 2013)
Okun and Suyemoto's book addresses theory and skills for continuing beyond the first few sessions with a client, thus helping students take the "next step" from a basic understanding of interviewing skills to a conceptualization of the counseling process. CONCEPTUALIZATION AND TREATMENT PLANNING FOR EFFECTIVE HELPING teaches students how to integrate the many pieces of the helping process (e.g., theoretical orientation, the person of the therapist, the person of the client, the contexts that affect the clients, the therapy relationship, the context of the therapy, the skills and resources available, etc.) into a conceptualization that will foster efficacy in creating positive change. CONCEPTUALIZATION AND TREATMENT PLANNING FOR EFFECTIVE HELPING teaches students how to integrate the many pieces of the helping process (e.g., theoretical orientation, the person of the therapist, the person of the client, the contexts that affect the clients, the therapy relationship, the context of the therapy, the skills and resources available, etc.) into a conceptualization that will foster efficacy in creating positive change
1. Exploring conceptualization -- 2. Exploring influences of personal worldviews -- 3. Conceptualization clients in contexts -- 4. Conceptualization therapeutic relationships -- 5. Dilemmas in effective helping -- 6. Beginning conceptualization : gathering and integrating information -- 7. Conceptualization, treatment planning, and diagnosis -- 8. Iterative conceptualization and treatment planning -- 9. Continuous evaluation and termination
Includes bibliographical references and index
Keywords: Education -- Counseling; PSYCHOLOGY / Psychotherapy / Counseling